BUDAYA KORPORAT DAN PRODUKTIVITAS KERJA KARYAWAN PT. BANK RAKYAT INDONESIA (PERSERO) CABANG TULUNGAGUNG - Ema Desia Prajitiasari; Thantawi A.S - -; Armanu - Thoyib (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT In the continuously operational management context and particularly on the long term perspective, human resources have an important role in creating and realizing business opportunity. Producing high level of integrity among professional employee demands called corporate culture for all participants of the company rely on the base while achieving the task. Competitive advantage of a company is productivity. The objective of this research to analyze effects of the corporate culture variables (integrity, professionalism, customer satisfaction, pattern, and reward to human resource) simultaneously and partially, on employee’s work productivity. Other analysis emphasizes on the dominant influential variables of corporate culture on employee’s work productivity. Method of Stratified Random Sampling was applied at the PT. Bank Rakyat Indonesia (Persero) Branch Office Tulungagung and select for 118 respondents. Hypothesis examination involves multiple regression analysis. The result of this research indicate that integrity, professionalism, customer satisfaction, pattern, and reward to human resource simultaneously and partially have positive influence on employee’s work productivity. This research result also shows that pattern has the dominant influence on employee’s work productivity. Keywords: corporate culture, employee’s work productivity.